(untitled) (Physical Education, Health and Social Sciences, 2025)
Although Pakistan has ratified the Convention on the Rights of the Child (CRC) and gone on to formulate provincial child protection laws, there still exist great gaps between the paper obligations and the actual conditions of vulnerable children in Punjab. Although the province has established several legal and policy frameworks after decentralization reforms, there are fears that their implementation has not been practical, the institutions have not been coordinated to enforce the policies and ensure their efficiency in child rights protection in the long run. The paper has critically analyzed the laws and policy frameworks on child protection in Punjab, in relation to the principles of the CRC. It also determined the effectiveness of the mechanisms of child welfare service delivery in facilitating and safeguarding the rights of the children, finding the institutional, administrative, and socio-cultural barriers that impede the implementation of the mechanisms, and suggested evidence-based recommendations to enhance coordination, accountability, and capacity-building in the child welfare institutions. The research design used was qualitative research based on the interpretivist paradigm to fill the gap between the legal provisions and their actual application in the welfare services. The research was in the most populous province in Pakistan and a major administrative unit in governing child welfare, Punjab, and with the main stakeholders having a child protection officer, a social welfare professional, a case manager, a legal practitioner, an NGO representative, and a policy official. The sampled information rich participants were selected using purposive method because the researcher was interested in individuals with first-hand experience in the delivery of child welfare services. The semi-structured interviews and document analysis allowed gathering data and exploring the nature of the institutional practices, processes of governance, and operational issues in a deeper way. Thematic analysis provided the methodological structure of coding and organizing the data into the primary themes connected to the legal alignment with the standards of the CRC, institutional capacity limitations, inter-agency coordination gaps, the barriers to socio-cultural success, and the effectiveness of service delivery. The results showed that despite the fact that the legal framework in terms of normative consistency with the principles of CRC are demonstrable, there is a deficiency of effective implementation through the weak mechanisms of its enforcement, a lack of professional capacity, and ineffective internal coordination structures, as well as cultural stigma. The research finds that the gap between the law and practice in Punjab needs concerted institutional changes, increased monitoring, professional training and community based prevention policy in order to effectively implement the child rights.